ANALISIS KONFLIK PARA TOKOH DAAM NOVEL PENA JINGGA KARYA WAHYU SUJANI - Ahmadi, Ahmadi; Martono, Martono; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study is a discussion of conflicts in the Pena Jingga novel by Wahyu Sujani. These conflicts are external conflicts and internal conflicts experienced by the characters in the Pena Jingga novel by Wahyu Sujani. This research was conducted by descriptive method. The form of this research is qualitative research. The approach used is the literary psychology approach to the stimulus model and response by Skinner. The technique of data collection is done by means of identification, and classification. The data collection tool used is the author as a key instrument, assisted by a data card. The technique of testing the validity of the data is the completeness of the supporting reference, peer examination, the conclusion of the results of the discussion, triangulation, and discussion with the supervisor. Data analysis technique is to critically read data, analyze and interpret external and internal conflict data, check data, and provide final conclusions of research. The results of this study are conflicts experienced by all external and internal figures. The results of this study can be implemented into Indonesian learning.Â Keywords: Characters, Conflict, Novels